Exploring Green Start-up Finance for Tourism Villages - Cening Ardina; I Putu Astawa; Nyoman Indah Kusuma Dewi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study aims to assess green start-up finance in developing tourism villages in Bali. Green start-up finance has the aim of maintaining tourism sustainability by promoting environmental conservation issues. Investors do not all have an initial goal towards green issues in building a business even though this issue is an important issue in maintaining business. Data is collected through two stages, namely debt interviews and questionnaires. The results of the qualitative analysis were used to create a questionnaire to be distributed to the tourism village manager. Eighty managers from one hundred who have answered questionnaires delivered via e-mail and mail. Quantitative data were analyzed using descriptive statistics. The results of a qualitative study that green start-up finance has not yet appeared in the beginning in supporting the environment that arises are problems of economic improvement. Quantitatively, the tourism village manager on average sixty-five percent agrees that in green start-up finance activities include environmentally friendly products/ services, product/ service features, reputation, customer types, innovativeness, entrepreneurial motivation, market orientation, company growth, strategic issues, institutional entrepreneurship. The results of this study provide an overview for the managers of many topics involved in implementing green start-up finance and are indispensable in maintaining sustainable village tourism. These results can be further developed by linking with the local culture and the village economy.